Improving Public Understanding of the Provisions for Child Detention in the Juvenile Criminal Justice System Based on Law Number 11 of 2012 - Mukhawas Rasyid; Jumra Jumra; Gustika Sandra (Journal of Universal Community Empowerment Provision, 2025)
According to the Child Protection Law (amended by Law Number 23 of 2002), a child is a person under 18 years of age, including unborn children. In the juvenile criminal justice system, based on the Juvenile Criminal Justice System Law, there are specific provisions regarding children in conflict with the law, including a specific age limit for criminal responsibility. Under Indonesian law, detention of children in conflict with the law can only be carried out as a last resort (ultimum remedium) and for the shortest possible time, because detention can have a serious impact on a child's development. The purpose of this Community Service is to discuss increasing public understanding of the provisions for child detention in the Juvenile Criminal Justice System based on Law Number 11 of 2012. The background of this research is based on the still low public understanding of the concept of child detention, which is essentially specific, strict, and makes detention a last resort (ultimum remedium). The method used is a qualitative method with a descriptive approach, through data collection techniques such as observation, interviews, and literature studies. The results of this community service program revealed that after the outreach program, there was an increase in public understanding, marked by increased awareness of the importance of child protection, reduced negative stigma, and increased support for a restorative justice approach. The conclusion of this study is that legal outreach plays an effective role in increasing public understanding regarding the provisions regarding child detention in the juvenile criminal justice system. Therefore, legal education activities need to be carried out continuously to create a legally aware society that supports the protection of children's rights.